Factors influence attitude of UiTM students towards online shopping / Anis Syahirah Mahyudin - Mahyudin, Anis Syahirah (Faculty of Business Management, 2016)
The purpose of this study is to identify the factors that influence attitude of UiTM students towards online shopping. The research is based on a sample of 317 respondents. The results show that perceived ease of use, perceived usefulness, and perceived enjoyment have significant influence on attitude of UiTM students towards online shopping. While perceived risk do not give impact on attitude towards online shopping among students from UiTM Kampus Bandaraya Melaka. The strongest relationship is between perceived enjoyment towards attitude towards online shopping.